PRO CONS THE EXISTENCE OF DEATH PENALTY IN CORRUPTION ACT OF 1999 IN INDONESIA - Anis Rifai (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Indonesia has 71 years building his conduct on the basis of civilization and cultural independence of the nation whose ideology Pancasila and the 1945 Constitution ideals to be realized is the realization of just and prosperous life of a nation that material and spiritual / devoted to God aimed as much as possible for the prosperity of the people. In realizing this, the problem of corruption is the biggest development and welfare of the Indonesian people. The lack of deterrent effect of criminal sanctions for the culprit causing the proliferation of perpetrators of corruption on all fronts. Under penalty of death penalty for perpetrators of corruption is considered to be one of the solutions deterrent for the perpetrators. Rules of the death penalty for perpetrators of corruption still causes a lot of pros and cons on the premises. In connection with this, this paper will outline the pros and cons of the existence of the implementation of the death penalty to cases of corruption in Indonesia.